Assessing Factors Influencing Online Shopping Adoption Among Indonesian Consumers: A Quantitative Study - Sudirjo, Frans; Tjahyadi, Indra (Westscience Press, 2023)
The adoption of online shopping has significantly increased in recent years, particularly in developing countries such as Indonesia. This study aims to assess the factors influencing the adoption of online shopping among Indonesian consumers. A quantitative research approach was used, and data were collected from 350 Indonesian consumers through a structured questionnaire. The results indicate that perceived usefulness, perceived ease of use, website design quality, trust in online shopping, online shopping experience, and website security are significant factors influencing online shopping adoption among Indonesian consumers. These findings suggest that online retailers and marketers should focus on enhancing the user-friendliness and safety of their online shopping platforms to increase consumer trust and adoption. Additionally, policymakers should consider further investing in improving e-commerce infrastructure and growing awareness about the benefits of online shopping to promote the adoption of online shopping among Indonesian consumers.